2017
DOI: 10.1155/2017/9525893
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis of the Mandible after Dental Implants in an Immunocompetent Patient

Abstract: Dental implants are now broadly used to replace missing teeth, and the presence of infectious complications is rising. Dental implant therapy as a local risk factor for the onset of osteomyelitis and its management have not been widely explored. Here, we report an unusual case of mandibular suppurative osteomyelitis caused by Streptococcus intermedius in a healthy and immunocompetent patient secondary to mandibular implants. We describe how surgery combined with systemic application of antibiotics allowed cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
3
0
5
Order By: Relevance
“…Sobre el tipo de osteomielitis diagnosticadas, los distintos estudios analizados presentan 13 cuadros crónicos (10,11,(15)(16)(17)(18)(19)(20) , 9 osteomielitis agudas (11,14,21) ; evidenciando que no hay una mayor diferencia entre los diagnósticos agudos y crónicos; resaltando que en los cuadros agudos todos los Implantes dentales fueron perdidos, mientras que cuando el tipo fue crónico se llegaron a conservar algunos Implantes.…”
Section: Tipos De Osteomielitis Antecedentes Patológicos Y Etiologíaunclassified
See 3 more Smart Citations
“…Sobre el tipo de osteomielitis diagnosticadas, los distintos estudios analizados presentan 13 cuadros crónicos (10,11,(15)(16)(17)(18)(19)(20) , 9 osteomielitis agudas (11,14,21) ; evidenciando que no hay una mayor diferencia entre los diagnósticos agudos y crónicos; resaltando que en los cuadros agudos todos los Implantes dentales fueron perdidos, mientras que cuando el tipo fue crónico se llegaron a conservar algunos Implantes.…”
Section: Tipos De Osteomielitis Antecedentes Patológicos Y Etiologíaunclassified
“…Respecto a los antecedentes patológicos 15 pacientes estaban sanos (sin historial médico), y 7 tenían antecedentes de ser fumadores, 6 son hipertensos, 5 son diabéticos, 2 sufren de asma, 2 de hipotiroidismo, 2 con Hipercolesterolemia, 1 con bronquitis crónica y pirosis, 1 con neutropenia leve, 1 con desorden bipolar, 1 con síndrome de sinovitis, acné, pustulosis, hiperostosis y osteítis (SAPHO)¸ pustulosis palmoplantar y osteosclerosis de la clavícula, 1 con osteoporosis, la que trata con bifosfonatos; y 1 presentaba Osteopetrosis. (10,11,(14)(15)(16)(17)(18)(19)(20)(21) . Por lo tanto, la presencia de la Os no necesariamente estaría relacionada a un antecedente patológico, sino que puede estar relacionado a algún factor local contaminante durante el procedimiento quirúrgico de instalación de los implantes dentales.…”
Section: Tipos De Osteomielitis Antecedentes Patológicos Y Etiologíaunclassified
See 2 more Smart Citations
“…We reported that in addition to our 5 cases, only 2 other cases among the 34 reported cases of DIOMJ in the literature were related to a pure S anginosus group infection. 2,3 It should be pointed out that Schlund et al 4 published a new case report of S anginosus DIOMJ, although in a polymicrobial context. Unfortunately, we could not include this reference in our study because it was published 1 month after our manuscript submission.…”
mentioning
confidence: 99%